Generation of Human Immunosuppressive Myeloid Cell Populations in Human Interleukin-6 Transgenic NOG Mice - Hanazawa, Asami; Ito, Ryoji; Katano, Ikumi; Kawai, Kenji; Goto, Motohito; Suemizu, Hiroshi; Kawakami, Yutaka; Ito, Mamoru; Takahashi, Takeshi (Frontiers in Immunology, 2018)
The tumor microenvironment contains unique immune cells, termed myeloid derived suppressor cells (MDSCs), and tumor-associated macrophages (TAMs) that suppress host anti-tumor immunity and promote tumor angiogenesis and metastasis. Although these cells are considered a key target of cancer immune therapy, in vivo animal models allowing differentiation of human immunosuppressive myeloid cells have yet to be established, hampering the development of novel cancer therapies. In this study, we established a novel humanized transgenic (Tg) mouse strain, human interleukin (hIL)-6-expressing NOG mice (NOG-hIL-6 transgenic mice). After transplantation of human hematopoietic stem cells (HSCs), the HSC-transplanted NOG-hIL-6 Tg mice (HSC-NOG-hIL-6 Tg mice) showed enhanced human monocyte/macrophage differentiation. A significant number of human monocytes were negative for HLA-DR expression and resembled immature myeloid cells in the spleen and peripheral blood (PB) from HSC-NOG-hIL-6 Tg mice, but not from HSC-NOG non-Tg mice. Engraftment of HSC4 cells, a human head and neck squamous cell carcinoma derived cell line producing various factors including IL-6, IL-1, macrophage colony-stimulating factor (M-CSF) and vascular endothelial growth factor (VEGF), into HSC-NOG-hIL-6 Tg mice induced a significant number of TAM-like cells, but few were induced in HSC-NOG non-Tg mice. The tumor-infiltrating macrophages in HSC-NOG-hIL-6 Tg mice expressed a high level of CD163, a marker of immunoregulatory myeloid cells, and produced immunosuppressive molecules such as arginase-1 (Arg-1), IL-10, and VEGF. Such cells from HSC-NOG-hIL-6 Tg mice, but not HSC-NOG non-Tg mice, suppressed human T cell proliferation in response to antigen stimulation in in vitro cultures. These results suggest that functional human TAMs can be developed in NOG-hIL-6 Tg mice. This mouse model will contribute to the development of novel cancer immune therapies targeting immunoregulatory/immunosuppressive myeloid cells.